Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1055/a-1224-3625
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Trends on Myricetin

Abstract: Myricetin is a member of the group of flavonoids called flavonols. Myricetin is obtained from various fruit, vegetables, tea, berries and red wine. Myricetin is characterized by the pysrogallol B-ring, and the more hydroxylated structure is known to be capable for its increased biological properties compared with other flavonols. Myricetin is produced by the Myricaceae, Anacardiaceae, Polygonaceae, Pinaceae and Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…Plant-based nutraceuticals can be found in common dietary sources in various forms and derivatives which may show different and/or more efficient bioactivities. Myricetin is a common phytochemical which is intensively studied for its bioactivities and still provides novel outcomes in terms of efficiency and effectiveness [10,17,18]. Therefore, derivatives of myricetin are also receiving increasing interest in this context where their potential bioactivities, action mechanisms, adverse effects, etc., are being continuously explored.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based nutraceuticals can be found in common dietary sources in various forms and derivatives which may show different and/or more efficient bioactivities. Myricetin is a common phytochemical which is intensively studied for its bioactivities and still provides novel outcomes in terms of efficiency and effectiveness [10,17,18]. Therefore, derivatives of myricetin are also receiving increasing interest in this context where their potential bioactivities, action mechanisms, adverse effects, etc., are being continuously explored.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that this genus possess antioxidant effect probably by controlling the over production of free radicals. The reduction in glucose level might be attributed to the detected myrecetin as it is responsible for the inhibition of I-kappa-B(IkB)/nuclear factor-kB (NF-KB) P65 signaling pathway (Gupta et al 2020). Myrecetin also possess the ability to alter phosphorylation of insulin receptor, subsequently effecting glucose transporters sub type 4 (GLUT-4) translocation (Li and Ding 2012).It also possess the potential to protect the beta cells against high glucose induced apoptosis by inhibition of endoplasmic stress probably by inactivation of CDK5 and subsequent upregulation of PDX-1 and SER CA2b (Gupta et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Beta-sitosterol were proved to be effective in ICH mainly by reducing the risk of plasma cholesterol and atherosclerosis [40]. Several pharmacological properties on Mandenol have been reported including attenuating the expression of pro-in ammatory factors [41], Gudiya et al have shown that Myricanone was equipped with the biological functions of antioxidant, antiin ammatory, and anti-ischemia-reperfusion injury [42]. In addition, aloe-emodin is a widely existing anthraquinone in nature, which has been found to lower cholesterol by inhibiting PCSK9 [43].…”
Section: Discussionmentioning
confidence: 99%